Effect of overexpression of wild-type and mutant Cu/Zn-superoxide dismutases on oxidative stress and cell death induced by hydrogen peroxide, 4-hydroxynonenal or serum deprivation: Potentiation of injury by ALS-related mutant superoxide dismutases and protection by Bcl-2 - Lee, M. (2013)
10.1046/j.1471-4159.2001.00417.x